Anastomotic leaks in colorectal surgery. Issue 10 (24th January 2014) - Damen, Nikki; Spilsbury, Katrina; Levitt, Michael; Makin, Gregory; Salama, Paul; Tan, Patrick; Penter, Cheryl; Platell, Cameron
Abstract Background Anastomotic leaks are a serious complication of bowel surgery. This study aimed to evaluate the rate and severity, and identify risk factors for leaks in patients undergoing bowel anastomoses. Methods Prospective evaluation was performed on patients undergoing bowel surgery within a colorectal surgical unit. Anastomotic leak was defined and graded according to severity. A nurse independently collected the information. Stepwise logistic regression analysis was performed. Results Two thousand three hundred and sixty‐three patients underwent 2994 anastomoses. Their median age was 64 years. Seven per cent were emergency operations. Anastomotic leak occurred in 82 patients (2.7%). Sixty‐three per cent of leaks were managed with drainage or re‐operation. Ultra‐low anterior resection (ULAR) was associated with the highest subgroup leak rate (7.3%). In multivariable analysis, independent predictors for a leak included 'other' pathologies (iatrogenic injury, ischaemia, radiation enteritis) (P = 0.016, odds ratio (OR): 6.3, 95% confidence interval (CI): 1.4–28.0), ULAR (P = 0.001, OR: 8.5, 95% CI: 2.3–31.2) and the surgeon (A: P < 0.001, OR: 3.4, 95% CI: 2.1–5.6). Conclusion Majority of predictors for anastomotic leak were fairly intuitive. Nonetheless, it was relevant to note the importance of the individual surgeon as an independent predictor for leaks.